2008
DOI: 10.1507/endocrj.k08e-026
|View full text |Cite
|
Sign up to set email alerts
|

Elevated High Sensitivity C-Reactive Protein Is Associated with Type 2 Diabetes Mellitus: The Persian Gulf Healthy Heart Study

Abstract: Abstract. Previous studies have suggested that low-grade systemic inflammation is involved in the pathogenesis of type 2 diabetes mellitus. However, limited information is available about the relationship of diabetes mellitus and inflammation in Asia. We examined the association between high-sensitivity C-reactive protein (CRP) levels and diabetes in a general Iranian population. In an ancillary study to the Persian Gulf Healthy Heart Study, a cohort study of men and women aged ≥25 years, a random sample of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…T2D has such an enormous cost in terms of quality of life and mortality as well as economic cost [2]. Despite more than 100 million patients affected worldwide and a dramatic socioeconomic burden due to vascular complications, the etiology of T2D is not yet completely understood [5]. It has been hypothesized that T2D is a manifestation of an ongoing acute-phase response that is primarily characterized by alterations of the so-called acute-phase proteins, such as C-reactive protein (CRP) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…T2D has such an enormous cost in terms of quality of life and mortality as well as economic cost [2]. Despite more than 100 million patients affected worldwide and a dramatic socioeconomic burden due to vascular complications, the etiology of T2D is not yet completely understood [5]. It has been hypothesized that T2D is a manifestation of an ongoing acute-phase response that is primarily characterized by alterations of the so-called acute-phase proteins, such as C-reactive protein (CRP) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperhomocysteinemia, known risk factor for coronary atherosclerosis (Okada et al, 1999), has also been shown to be detrimental to pancreatic insulin secretion (Patterson et al, 2006). The C-reactive protein (CRP), an inflammatory marker that confers increased risk for atherosclerosis (Hayaishi-Okano et al, 2002), is increased in T2D patients (Nabipour et al, 2008) and obese subjects (Richardson et al, 2009), and also relates to the control of diabetes (King et al, 2003), i.e. may increase due to the weight gain caused by intensive control of diabetes (Schaumberg et al, 2005).…”
Section: Prevalence (%)mentioning
confidence: 99%
“…The design of this study encompasses two major components: phase I is a crosssectional prevalence study of unhealthy lifestyle and ischemic heart disease and associated risk factors, and phase II is a multiple interventional project for reduction of cardiovascular diseases in the region. Detailed information about the methods and procedures of this study is available elsewhere [28]. In an ancillary study to the Persian Gulf Healthy Heart Study, a total of 1754 (49.2% males, 50.8% females) subjects were selected through a stratified multistage design from major ports of Bushehr Province (an Iranian province with the greatest boarder with the Persian Gulf).…”
Section: Community Sampling and Baseline Examinationsmentioning
confidence: 99%